Adverse Events and Reinterventions Following Pancreatic Endoscopic Sphincterotomy. Issue 7 (August 2018) - Dufault, Darin L.; Elmunzer, B. Joseph; Cotton, Peter B.; Williams, April; Cote, Gregory A.
Abstract : Objectives: Pancreatic endoscopic sphincterotomy (PES) is an independent risk factor for short- and long-term adverse events (AEs) of endoscopic retrograde cholangiopancreatography. We sought to measure PES-specific AEs and trends in the use of PES. Methods: This was a retrospective cohort of consecutive patients who underwent first-time PES between June 2008 and June 2015. Indications for PES were dichotomized: (1) structural pathology (chronic pancreatitis and local complications of acute pancreatitis) and (2) suspected sphincter pathology (idiopathic recurrent acute pancreatitis and sphincter of Oddi dysfunction). Rates of AEs and pancreatic orifice reinterventions were measured, with reintervention rates limited to those having a minimum of 12-month follow-up. Results: Of 567 patients, 198 (34.9%) underwent PES for structural and 369 (65.1%) for suspected sphincter pathology. Rates of post–endoscopic retrograde cholangiopancreatography pancreatitis and unplanned hospitalization were high when PES was originally performed for suspected sphincter pathology (12.6% and 14.6%, respectively). The overall reintervention rate was 28.9% and significantly greater for sphincter (41.7%) compared with structural pathology (13.5%, P = 0.005). Conclusions: The likelihood of reintervention after PES is high, particularly when the primary indication is suspected sphincter pathology such as idiopathic recurrent acute pancreatitis. Further prospective studies are needed to clarify if and when this maneuver confers significant benefit to patients.